Miscellaneous essays - Colebrooke, H. T. (Trübner, 1873)
V. 1. The life of H. T. Colebrooke, by his son, Sir T. E. Colebrooke.--v. 2-3. Miscellaneous essays, by H. T. Colebrooke. A new ed., with notes, by E. B. Cowell.